2019
DOI: 10.1134/s0026893319060074
|View full text |Cite
|
Sign up to set email alerts
|

40 Years of Studying RNA Import into Mitochondria: From Basic Mechanisms to Gene Therapy Strategies

Abstract: Mitochondria of many living species internalize nuclear DNA-encoded ribonucleic acids. The pools of imported RNA molecules, as well as fine mechanisms of these processes, are highly species-specific. To date, baker's yeast Saccharomyces cerevisiae are the best studied in this regard. Moreover, the processes of yeast RNA mitochondrial import have been the basis of modeling several gene therapy strategies aimed to palliate negative effects of pathogenic mutations in human mitochondrial DNA. In this review, we su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Something similar was already successfully tested by intranasal administration of growth factors for treating other brain injuries [ 210 , 211 , 212 ]. In addition, new pieces of evidence report important advancements in the delivery of oligonucleotides and nucleic acids in general in several biological models [ 213 , 214 ], by using liposomes and/or specific peptides for mitochondrial delivery [ 215 , 216 , 217 , 218 , 219 ], coherently with the recent mRNA-based vaccine success [ 220 , 221 ] and advances in the analysis of mitochondrial tRNA import [ 222 , 223 , 224 , 225 ].…”
Section: Mds Depending On Aa-trna Mutations or Aa-trna Synthetase Mut...mentioning
confidence: 99%
“…Something similar was already successfully tested by intranasal administration of growth factors for treating other brain injuries [ 210 , 211 , 212 ]. In addition, new pieces of evidence report important advancements in the delivery of oligonucleotides and nucleic acids in general in several biological models [ 213 , 214 ], by using liposomes and/or specific peptides for mitochondrial delivery [ 215 , 216 , 217 , 218 , 219 ], coherently with the recent mRNA-based vaccine success [ 220 , 221 ] and advances in the analysis of mitochondrial tRNA import [ 222 , 223 , 224 , 225 ].…”
Section: Mds Depending On Aa-trna Mutations or Aa-trna Synthetase Mut...mentioning
confidence: 99%
“…Additionally, the administration of RP/KALA-MITO-Porter did not alter the biomarker levels in mouse serum, suggesting its good biocompatibility for in vivo applications. However, as mammalian mitochondria, in which mitochondrial tRNA (tRNA) is supplied by mtDNA, do not import RNA molecules from the cytoplasm, unlike yeast and plant mitochondria, some researchers have questioned the mechanism by which mammalian mitochondria accomplish this cellular process. Some studies have claimed that RNA is internalized into mammalian mitochondria from the cytoplasm. Thus, further investigation into the mechanism by which nucleic acids enter mammalian mitochondria is necessary.…”
Section: Mitochondrial Gene Deliverymentioning
confidence: 99%
“…Alternatively, the mitochondria could itself start viral protein synthesis with ribosomes located at the MOM 83 , and/or uptake vRNA from the cytoplasm after virus entry and vRNA release into the cytoplasm, although the former would require mitochondria localization sequences in those translocated molecules. In this regard, it is known that mitochondria are capable to import RNA from the cytoplasm through a pathway that involves the TOM/TIMM complex 84 , and SARS-CoV-2 RNA is predicted to locate at this organelle 71 . Indeed, this has been confirmed in a recent work published during the review of this manuscript that demonstrated that TOM20 mediates vRNA entry into mitochondria and that it is not colocalized with ER and lysosomal markers 33 .…”
Section: Mitochondria Infection By Vrnamentioning
confidence: 99%